Between two moons : a novel - Abdel Gawad, Aisha (Doubleday, 2023)
"A deeply moving family story about identity, faith, and belonging set in the Muslim immigrant enclave of Bay Ridge, Brooklyn following three siblings coming of age over the course of one Ramadan. It's the holy month of Ramadan, and twin sisters Amira and Lina are about to graduate high school in Bay Ridge, Brooklyn. On the precipice of adulthood, they plan to embark on a summer of teenage revelry, trying on new identities and testing the limits of what they can get away with while still under their parents' roof. But the twins' expectations of a summer of freedom collide with their older brother's return from prison, whose mysterious behavior threatens to undo the delicate family balance. Meanwhile, outside the family's apartment, a storm is brewing in Bay Ridge. A raid on a local business sparks a protest that brings the Arab community together, and a senseless act of violence threatens to tear them apart. Everyone's motives are called into question as an alarming sense of disquiet pervades the neighborhood. With everything spiraling out of control, how will Amira and Lina know who they can trust? A gorgeously written, intimate family story and a polyphonic portrait of life under the specter of Islamophobia, Between Two Moons challenges the reader to interrogate their own assumptions, asking questions of allegiance to faith, family, and community, and what it means to be a young Muslim in America"--